2009
DOI: 10.1111/j.1600-0404.1990.tb01619.x
|View full text |Cite
|
Sign up to set email alerts
|

Vibration sensitivity thresholds: methodological considerations

Abstract: Aaserud 0, Juntunen J, Matikainen E. Vibration sensitivity thresholds: methodological considerations. sense tests made in a semiquantitative way with a 128 stuning fork.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 11 publications
2
6
1
1
Order By: Relevance
“…However, this observation is in accordance with other studies [1,29,36,41]. Sources for large variations in sensitivity may be many.…”
Section: Discussionsupporting
confidence: 82%
“…However, this observation is in accordance with other studies [1,29,36,41]. Sources for large variations in sensitivity may be many.…”
Section: Discussionsupporting
confidence: 82%
“…Our values in the same frequencies were between 104 and 111 µN for OI prostheses, 108 and 123 µN for socket-suspended prostheses, and 95 and 112 µN for the intact limb ( Table 2). Aaserud et al showed higher vibrometric thresholds on the upper than the lower limb in a study assessing 12 nondisabled subjects [30]. The results from Aaserud et al could explain why our values for the intact limb were somewhat lower than those reported by Lundborg et al [29].…”
Section: Discussioncontrasting
confidence: 55%
“…Sensibility studies using vibration as stimuli have shown that mechanoreceptors in the skin can detect vibration frequencies between 0.4 and 800 Hz [27]. However, most published clinical data are from studies on patients with various type of neuropathic conditions [28][29], and in those studies, vibration frequencies between 20 and 250 Hz have been used as stimuli [28][29][30]. In patients with transfemoral amputation (TFA), testing sensation in terms of vibration seems to be one natural choice since vibration is one type of stimuli the patient hypothetically can experience when the prosthetic foot strikes the ground.…”
Section: Introductionmentioning
confidence: 99%
“…Maeda and Griffin [6] compared acceleration thresholds from various studies addressing passive touch, finding that most of them are in the range 105-115 dB for sinusoidal stimuli ranging from 100 to 250 Hz. The lowest reported acceleration thresholds are 97-98:5 dB, for contact areas (probe size) ranging from 53 to 176:7 mm 2 [30], [31], [32]. It is worth noticing that the widely accepted results by Verrillo [17] report lowest displacement thresholds of approximately À20 dB (re 10 À6 m) at 250 Hz, equivalent to about 105 dB rms acceleration.…”
Section: Interpretation Of Resultsmentioning
confidence: 94%